2012
DOI: 10.1002/chem.201103530
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Total Synthesis of Deoxyschizandrin and Exploration of Its Antiproliferative Effects and those of Structurally Related Derivatives

Abstract: The natural product deoxyschizandrin has been shown to have a wide range of biological activities. In recent years the therapeutic potential of this compound against cancers has attracted significant interest. Herein we describe a concise de novo total synthesis of deoxyschizandrin based around a double organocuprate oxidation strategy. In addition, we present the results of biological studies exploring the ability of deoxyschizandrin and synthetic precursors lacking the medium ring biaryl unit to inhibit the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Intriguingly, a recent study has found that SchA has relatively little effects upon proliferation relative to its novel and nonnatural derivative that lacks the medium ring biaryl architecture. [ 27 ] Accordingly, we were stimulated to speculate that SchA exhibits an extensive scope of biological activities, which might be related to its structural characteristics. Definitely, the disparity of this sensitivity in different cells might contribute to the inconsistent consequences, which has been elaborated in a study of schizandrin.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, a recent study has found that SchA has relatively little effects upon proliferation relative to its novel and nonnatural derivative that lacks the medium ring biaryl architecture. [ 27 ] Accordingly, we were stimulated to speculate that SchA exhibits an extensive scope of biological activities, which might be related to its structural characteristics. Definitely, the disparity of this sensitivity in different cells might contribute to the inconsistent consequences, which has been elaborated in a study of schizandrin.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing with the published data and the UV spectra of standards, peaks 1–5 were identified as schisandrin, gomisin A, schisantherin B, deoxyschisandrin, and γ‐schisandrin, respectively.…”
Section: Resultsmentioning
confidence: 66%
“…SchA belongs to the dibenzocyclooctadiene family of lignans (49). Its main feature is that the biaryl units are connected via aliphatic chains to form an eight-membered ring carbon skeleton (50).…”
Section: Resultsmentioning
confidence: 99%